2016
DOI: 10.2218/jls.v3i3.1640
|View full text |Cite
|
Sign up to set email alerts
|

Querns and mills during Roman times at the northern frontier of the Roman Empire (Belgium, Northern France, Southern Netherlands, Western Germany): Unraveling geological and geographical provenances, a multidisciplinary research project

Abstract: This paper presents the results of a multi-disciplinary provenance study of querns and millstones during the Roman period (1st-4th century CE) in the northern part of the Roman Empire (provinces of Gallia Belgica and Germania Inferior). Comparative petrographical, mineralogical and geochemical analysis allowed an international team of archaeologists and geologists to identify the different raw materials used for the manufacturing of querns and millstones. As a result, (litho-) stratigraphic assignments as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition to the better-known volcanic rocks from the Eifel region used for the production of mills (Gluhak & Hofmeister, 2009, 2011, our study revealed the frequent occurrence of different types of sedimentary rocks: Ypresian sandstones and puddingstones from the north-western Paris Basin (Picavet et al, 2011), Lutetian limestones from the northern Paris Basin (Robert & Landréat, 2005), Thanetian quartzarenites from the Flemish Basin (Grès de Grandglise-Blaton: Reniere et al, 2016). The present paper focuses on the characterization and provenance of a particular group of conglomerates and coarse sandstones observed throughout the Roman provinces of Gallia Belgica and Germania inferior, an area that covers today the neighbouring regions of northern France, Belgium, Grand Duchy of Luxembourg, southern Netherlands and western Germany (Fig.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition to the better-known volcanic rocks from the Eifel region used for the production of mills (Gluhak & Hofmeister, 2009, 2011, our study revealed the frequent occurrence of different types of sedimentary rocks: Ypresian sandstones and puddingstones from the north-western Paris Basin (Picavet et al, 2011), Lutetian limestones from the northern Paris Basin (Robert & Landréat, 2005), Thanetian quartzarenites from the Flemish Basin (Grès de Grandglise-Blaton: Reniere et al, 2016). The present paper focuses on the characterization and provenance of a particular group of conglomerates and coarse sandstones observed throughout the Roman provinces of Gallia Belgica and Germania inferior, an area that covers today the neighbouring regions of northern France, Belgium, Grand Duchy of Luxembourg, southern Netherlands and western Germany (Fig.…”
Section: Introductionmentioning
confidence: 76%
“…Our research project involves a team of geologists and archaeologists (e.g. Williams-Thorpe & Thorpe, 1989;Gluhak & Hofmeister, 2009;Cnudde et al, 2013;De Kock et al, 2015;Reniere et al, 2016). Its first objective is to characterize the raw materials of the querns and millstones, in order to differentiate between groups of similar lithology; additionally, geological and geographical provenances need to be traced by comparison with local and regional geomaterials taken from collections and sampled in the 1 Milling stone: grinding stone in general (FR: meule).…”
Section: Introductionmentioning
confidence: 99%
“…The size of these diffusion zones depends on the sociopolitical situation (e.g., political stability and administrative boundaries), as well as the geographic settings (e.g., relief configuration and presence of fluvial corridors) and the availability of adequate geological materials (e.g., D. A. Bone, 2016; Reniere et al, 2016; Storemyr & Heldal, 2017; Turmel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One such trend that was reflected in the papers presented during the 1 st AGSTR meeting at the University of Haifa, and visible in this JLS issue, is an increase in the number of papers dealing with ground stone quarries, production, and design (e.g. Another trend gaining strength is a focus on geochemistry and provenance, distribution, and exchange (e.g., Williams-Thorpe 1988;Philip & Williams-Thorpe 2001;Watts et al 2004;Antonelli & Lazzarini 2010;Tsoraki 2011;Rosenberg & Golani 2012;Gluhak & Rosenberg 2013;Gluhak & Schwall 2015;Gluhak et al 2016;Reniere et al 2016). Efforts to understand the functions of stone items continue through increasingly sophisticated functional use-wear analyses (e.g., Hamon 2008;Risch 2008;Verbaas & van Gijn 2008;Delgado-Raack et al 2009;Bofill 2012;Adams 2014;Asryan et al 2014;Adams 2015;Delgado-Rack & Risch 2016;Groman-Yaroslavski et al 2016;Hamon 2016) and residue studies (e.g., Yohe II et al 1991;Hard et al 1996;Fullagar & Field 1997;Veth et al 1997;Piperno & Holst 1998;Perry 2004;Aranguren et al 2007;Barton 2007;Fullagar et al 2008;Buonasera 2016;Öğüt 2016).…”
mentioning
confidence: 99%